Nanocellulose-based adsorbent from pandan leaves for copper ions removal from wastewater - Haziqatulhanis, Ibrahim (2023)
A good selection of solid sorbent is one of the greatest problems in adsorption techniques in elimination of heavy metals. This project investigated the potential of nanocellulose sourced from pandan leaves as an adsorbent for Copper (II) ions removal from synthetic wastewater. Nanocellulose extraction was performed by carrying out chemical pre-treatments and sulphuric acid hydrolysis method before grafting with vinyl monomer acrylamide at grafting duration of 60 minutes and initiator ceric ammonium nitrate (CAN) amount of 0.7g. Scanning electron microscope (SEM), Fourier Transform Infrared (FTIR) spectroscopy, and X-Ray Diffractor (XRD) were employed to evaluate the morphology and functionality of the adsorbent surface, as well as its crystallinity. The removal of Copper (II) ions was observed using an atomic absorption spectrometer (AAS), in which the three parameters of pH variation, initial concentration, and adsorbent dosage were studied accordingly. Adsorption behavior of Copper (II) ions onto surface of nanocellulose and grafted nanocellulose were evaluated using Langmuir and Freundlich model isotherm. The optimal conditions for metal removal were determined to be at pH 6, with an initial metal concentration of 30 ppm and an adsorbent dosage of 2.2 g/L. The results demonstrated a maximum adsorption capacity of 8.19 mg/g for ungrafted nanocellulose and 15.22 mg/g for grafted nanocellulose. Based on the result, nanocellulose derived from Pandan leaves grafted with acrylamide monomer showed higher removal performance of Copper (II) ions compared to ungrafted sample. Several recommendations for further study were made such as testing the developed grafted nanocellulose in binary metal removal, conducting the study in column adsorption and regeneration studies of the nanocellulose-based adsorbent.